Pre-service primary teachers' views and use of technology in mathematics lessons - Muhammet Sahal; Ahmet Sukru Ozdemir (Association for Learning Technology, 2020)
Pre-service teachers who are future practitioners of the curriculum cannot be considered independent of their views on education and technology. The goal of this study is to determine the use of technology and the opinions of pre-service primary teachers (PPTs) regarding the use of technology in classroom activities in mathematics lessons. The research was conducted with 62 PPTs studying in a state university. The study is based on a case study. The PPTs designed and implemented activities with respect to the objective(s) in the primary school mathematics-teaching programme. These activities were observed and recorded in video. At the end of the semester, the opinion form prepared by the researchers was applied to the PPTs. Descriptive statistics, descriptive analysis and content analysis methods were used in the analysis of the data. According to the findings of the research, almost all of the PPTs expressed opinions about the positive and negative aspects of technology usage related to education. Furthermore, while 83.86% of the PPTs indicated that they wanted to use technology effectively in their professional lives in the future, only 19.35% of the observed activities benefited from the technology. PPTs advocated two main reasons for not using technology in classroom activities. The first was that concrete material is more effective where physical conditions are inadequate and the difficulty in accessing materials, especially at schools in rural areas. The second main reason concerned time constraints while following the curriculum.